Pengaruh CAR, NPL, ROA, ROE, dan LDR terhadap Penyaluran Kredit Perbankan (Studi Kasus pada Bank BPR di Wilayah Brebes Periode Tahun 2014-2018) - Devi Ade Yulian; Nasiruddin; Roby Setiadi; Khalid Iskandar; Mohammad Badrun Zaman (Universitas Muhadi Setiabudi, 2019)
Banking is an important part that plays a role in a country's economic development. Banking also functions as an intermediation institution whose task is to collect funds from the public and distribute them again to the public in the form of credit. In disbursing credit, there are internal factors that must be considered, namely in terms of capital proxied with the Capital Adequacy Ratio (CAR), the level of coliability proxied by Non-Performing Loans (NPL), profitability proxied with Return On Asset (ROA), dividend level proxied with Return On Equity (ROE), and in terms of banking liquidity proxied by Loan to Deposit Ratio (LDR). This study aims to analyze the effect of CAR, NPL, ROA), ROE and LDR on banking lending to People's Credit Bank (BPR) companies. The sample used in this study amounted to 6 banking companies. The analysis used is multiple linear regression. Based on the analysis that has been carried out, it was found that partially the ratio of CAR, NPL, ROA, ROE, LDR has a significant positive effect on bank lending.